Using Confidence Intervals for Assessing Reliability of Real Tests. (October 2019) - Oosterwijk, Pieter R.; van der Ark, L. Andries; Sijtsma, Klaas
Test authors report sample reliability values but rarely consider the sampling error and related confidence intervals. This study investigated the truth of this conjecture for 116 tests with 1, 024 reliability estimates (105 pertaining to test batteries and 919 to tests measuring a single attribute) obtained from an online database. Based on 90% confidence intervals, approximately 20% of the initial quality assessments had to be downgraded. For 95% confidence intervals, the percentage was approximately 23%. The results demonstrated that reported reliability values cannot be trusted without considering their estimation precision.